O Ages and Stages Questionnaires Brasil (ASQ-BR) no monitoramento do desenvolvimento de crianças de 5 a 50 meses de idade que frequentam centros de educação infantil - Ramos, Maysa Marinho Antunes (Universidade Federal de São Carlos, 2018)
It is well known that early childhood care is crucial to the development of the child. Thus, the demand for quality public services is made factual, considerably increasing the diligence for day-care centers and pre-schools. Kindergartens and preschools constitute development contexts with unique potentialities, since they bring together and accompany a large number of children from time to time and are therefore an important space for monitoring children's development. In Brazil, the scarcity of specific instruments for monitoring child development is a problem, since the number of children at risk of delay is relatively high. Recently adapted to the Brazilian context, the Ages and Stages Questionnaires Brazil (ASQ-BR) has been referred to internationally as an excellent instrument for monitoring child development, demonstrating good psychometric properties. It is in this sense that the present project aims to outline the overall development profile of children from 5 to 50 months of age who attend the Municipal Child Education Centers of a municipality in the interior of São Paulo, through ASQ-BR. For this, the educators applied the instrument with 392 children, whose performance was analyzed quantitatively. As a result, it was obtained that, in general, 97.96% of the children were born at term, 51.79% are female and are located in the questionnaires from 36 to 48 months. Girls performed better than boys in all categories, but this difference was only statistically significant in the categories: Fine Motor Co-ordination and Personal-Social Coordination. The highest scores were obtained in the category of Large Motor Coordination, Communication and Problem Solving, and the lowest scores were in the Personal-Social category and the Fine Motor Coordination category. The two categories with the highest incidence of delays were the Personal-Social category and the Fine Motor Coordination category, respectively. As for the applicability of the instrument in the context of early childhood education, by educators, it was clear the importance of monitoring child development, especially by these professionals and the need for complementary instruments that allow a more targeted look at the individuality of each child. In addition, the ASQ-BR was identified by these professionals as an important source of information that, in the course of the research, reverberated positively in professional practice and, consequently, in the development of the participating children.
Ages and stages questionnaires Brazil (ASQ-Br) no monitoring the development of children from 5 to 50 age months frequenting education centers infantile
Keywords: Desenvolvimento infantil; Monitoramento; Ages and Stages Questionnaires Brasil (ASQ-BR); Educação infantil; Child development; Monitoring; Ages and Stages Questionnaires Brazil (ASQ-BR); Child education; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL